The Impact of Leadership Change on Adaptation, Work Discipline in Increasing Effectiveness and Efficiency of Services in Tellumpanua Village, Tanete Rilau District, Barru Regency - Asriani, Asriani (LPPPIPublishing, 2024)
This study aims to evaluate and improve the implementation of Democratic and Effective Village Government in accordance with Law Number 6 of 2014 concerning Villages, especially in Tellumpanua Village. The main focus of this study is to identify inhibiting factors in the implementation of the policy and provide relevant recommendations. The research method used is qualitative research with a case study approach, which involves data collection through in-depth interviews, participant observation, and document analysis. The collected data were analyzed using a thematic analysis approach to identify patterns, themes, and key issues that emerged. The results of the study are expected to provide deeper insight into the challenges faced in implementing village policies and offer practical recommendations to improve and enhance the effectiveness of village government under the applicable legal framework. This study aims to strengthen the implementation of a more democratic village government and use authority effectively, which can ultimately contribute to the development and welfare of village communities.